Functional and structural differences in the hippocampus associated with memory deficits in adult survivors of acute lymphoblastic leukemia12. Issue 2 (8th August 2012) - Monje, Michelle; Thomason, Moriah E.; Rigolo, Laura; Wang, Yalin; Waber, Deborah P.; Sallan, Stephen E.; Golby, Alexandra J.
Abstract Background Radiation and chemotherapy targeted to the central nervous system (CNS) can cause cognitive impairment, including impaired memory. These memory impairments may be referable to damage to hippocampal structures resulting from CNS treatment. Procedure In the present study, we explored episodic memory and its neuroimaging correlates in 10 adult survivors of childhood acute lymphoblastic leukemia (ALL) treated with cranial radiation therapy and both systemic and intrathecal chemotherapy and 10 controls matched for age and sex, using a subsequent memory paradigm after episodic encoding of visual scenes. Results We report behavioral, structural, and functional changes in the brains of the adult survivors. They demonstrated poorer recognition memory, hippocampal atrophy, and altered blood oxygenation level‐dependent (BOLD) signal in the hippocampus. Whole brain statistical map analysis revealed increased BOLD signal/activation in several brain regions during unsuccessful encoding in ALL survivors, potentially reflecting ineffective neural recruitment. Individual differences in memory performance in ALL participants were related to magnitude of BOLD response in regions associated with successful encoding. Conclusions Taken together, these findings describe long term neuroimaging correlates of cognitive dysfunction after childhood exposure to CNS‐targeted cancer therapies, suggesting enduring damage to episodic memory systems. Pediatr Blood Cancer 2013;60:293–300. © 2012 Wiley Periodicals, Inc.